1988
DOI: 10.1210/mend-2-6-512
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Releasing Hormone- Induced Rise in Cytosolic Free Ca2+Levels: Mobilization of Cellular and Extracellular Ca2+Pools and Relationship to Gonadotropin Secretion

Abstract: Addition of GnRH to pituitary gonadotrophs preloaded with Quin 2 resulted in a rapid (approximately 8 s) mobilization of an ionomycin-sensitive intracellular Ca2+ pool. A second component of Ca2+ entry via voltage dependent channels contributed about 45% of the peak cytosolic free Ca2+ concentration ([Ca2+]i). Thereafter, influx of Ca2+ via voltage-sensitive and -insensitive channels is responsible for maintenance of elevated [Ca2+]i during the second phase of GnRH action. Addition of inositol 1,4,5-trisphosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 31 publications
2
39
0
Order By: Relevance
“…In exploring this, we have found that sustained stimulation of T3-1 cells with GnRH causes a pronounced desensitisation of Ca 2+ responses (McArdle et al 1995(McArdle et al , 1996. In control cells, GnRH causes a spike-plateau type increase in the cytosolic [Ca 2+ ] I concentration in which the spike phase reflects IP 3 -mediated mobilisation of Ca 2+ from intracellular stores and the plateau phase reflects entry of Ca 2+ across the plasma membrane (McArdle et al 1992), as previously reported for primary cultures of rat pituitary cells (Naor et al 1988). Focusing on the mobilisation of intracellular Ca 2+ , we observed a relatively rapid desensitisation of GnRH-stimulated Ca 2+ mobilisation (Fig.…”
Section: Desensitisation Downstream Of the Gnrh-rsupporting
confidence: 85%
“…In exploring this, we have found that sustained stimulation of T3-1 cells with GnRH causes a pronounced desensitisation of Ca 2+ responses (McArdle et al 1995(McArdle et al , 1996. In control cells, GnRH causes a spike-plateau type increase in the cytosolic [Ca 2+ ] I concentration in which the spike phase reflects IP 3 -mediated mobilisation of Ca 2+ from intracellular stores and the plateau phase reflects entry of Ca 2+ across the plasma membrane (McArdle et al 1992), as previously reported for primary cultures of rat pituitary cells (Naor et al 1988). Focusing on the mobilisation of intracellular Ca 2+ , we observed a relatively rapid desensitisation of GnRH-stimulated Ca 2+ mobilisation (Fig.…”
Section: Desensitisation Downstream Of the Gnrh-rsupporting
confidence: 85%
“…The results imply that digitonin permeabilization is accompanied by loss of exocytotic components in addition to PKC. Furthermore, GnRH stimulation of gonadotropin secretion is most likely mediated by PKC (27)(28)(29)(30)(31)(32) and by other messenger molecules such as Ca2" and arachidonic acid and/or its metabolites as discussed elsewhere (33)(34)(35)(36)(37). However, since the exocytotic response elicited by PMA in normal cells ( Fig.…”
Section: Discussionmentioning
confidence: 92%
“…receptor results in IP3-mediated increases in intracellular calcium which have been shown to be the primary signal for exocytosis in ␣T3-1 cells and primary gonadotropes (7)(8)(9). Calcium influx through the plasma membrane is thought to play a role in maintaining intracellular calcium stores.…”
Section: Gnrh-induced Activation Of Jnk Is Not Inhibited By Acute Chementioning
confidence: 99%
“…Extracellular calcium enters the cell through VGCCs in the plasma membrane while IP3 releases calcium from intracellular stores. The IP3-released calcium has been shown to be the critical signal required for secretion of the gonadotropic hormones, luteinizing hormone, and follicle-stimulating hormone (7,8). Influx of calcium through L-and T-type VGCCs is initiated independently from the IP3-mediated signal, but calcium influx through the plasma membrane is ultimately required for replenishment of intracellular stores (9).…”
mentioning
confidence: 99%